The CPO Transforming Procurement in the Real World - Schuh, Christian; Strohmer, Michael F.; Easton, Stephen; Scharlach, Armin; Scharbert, Peter; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
In the novel The CPO: Transforming Procurement in the Real World, we meet Thomas Sutter, a German-American living in Dusseldorf and working as a procurement manager for a major global automobile manufacturer, Autowerke. On a chance encounter while flying to Chicago, he meets the CEO of Heartland, a major food company in the U.S. Sutter impresses the CEO with his knowledge and, after a whirlwind courtship, he joins Heartland as its new Chief Procurement Officer, based in Fort Wayne, Indiana. Hired to transform procurement at Heartland, Sutter has an enormous challenge: to bring its procurement practices into the 21st century and save the company $5 billion. Despite the knowledge and experience he gained at Autowerke, Sutter fights over the next 18 months to find his place at Heartland, institute world-class procurement models and methods, win over the procurement teams and senior executives, and meet his goal. At first, his reputation--and his marriage--suffer, along with the company's overall sales and revenue. Can he pull a rabbit out of the hat? The CPO: Transforming Procurement depicts the real-life challenges of transforming procurement, while demonstrating the benefits of innovative procurement and leadership methods. Written by global thought leaders in A.T. Kearney's procurement and supply management practice--consultants who have helped numerous companies chop billions of dollars in costs out of their procurement budgets--The CPO will prove invaluable for those in purchasing and procurement. It will also present essential information to those in the C suite looking for ways to boost profits and productivity. The CPO: Portrays best-in-class, real-life, actionable methods to turn procurement into a function that can save billions and improve the bottom line.  Provides a fun way to learn essential lessons in procurement and change management. Shows how rejecting victimhood in all its aspects leads to personal and business success. Presents lessons in novel format--like The Goal, Who Moved My Cheese, The Five Dysfunctions of a Team, and others--to engage you and show techniques in action. .
Keywords: Business; Management science; Business and Management, general